Long-Term Opioid Use Following Surgery for Symptomatic Neuroma - Lans, Jonathan; Westenberg, Ritsaart F.; Gottlieb, Rachel E.; Valerio, Ian L.; Chen, Neal C.; Eberlin, Kyle R. (Journal of Reconstructive Microsurgery, 2021)
Background Identifying patients at risk for prolonged opioid use following surgery for symptomatic neuroma would be beneficial for perioperative management. The aim of this study is to identify the factors associated with postoperative opioid use of >4 weeks in patients undergoing neuroma surgery.Methods After retrospective identification, 77 patients who underwent surgery for symptomatic neuroma of the upper or lower extremity were enrolled. Patients completed the Patient-Reported Outcomes Measurement Information System (PROMIS) depression, Numeric Rating Scale (NRS) pain score, and a custom medication questionnaire at a median of 9.7 years (range: 2.5–16.8 years) following surgery. Neuroma excision followed by nerve implantation (n = 39, 51%), nerve reconstruction/repair (n = 18, 23%), and excision alone (n = 16, 21%) were the most common surgical treatments.Results Overall, 27% (n = 21) of patients reported opioid use of more than 4 weeks postoperatively. Twenty-three patients (30%) reported preoperative opioid use of which 11 (48%) did not report opioid use for >4 weeks, postoperatively. In multivariable logistic regression, preoperative opioid use was independently associated with opioid use of >4 weeks, postoperatively (odds ratio [OR] = 4.4, 95% confidence interval [CI]: 1.36–14.3, p = 0.013).Conclusion Neuroma surgery reduces opioid use in many patients but patients who are taking opioids preoperatively are at risk for longer opioid use. Almost one-third of patients reported opioid use longer than 4 weeks, postoperatively.
Keywords: neuroma; opioid; neuroma surgery